Interaction of shear and normal stresses in multiaxial fatigue damage analysis - Nicholas R. Gates; Ali Fatemi (Fracture and Structural Integrity)
Due to the abundance of engineering components subjected to complex multiaxial loading histories, being able to accurately estimate fatigue damage under multiaxial stress states is a fundamental step in many fatigue life analyses. In this respect, the Fatemi-Socie (FS) critical plane damage parameter has been shown to provide excellent fatigue life correlations for a variety of materials and loading conditions. In this parameter shear strain amplitude has a primary influence on fatigue damage and the maximum normal stress on the maximum shear plane has a secondary, but important, influence. In this parameter, the maximum normal stress is normalized by the material yield strength in order to preserve the unitless feature of strain. However, in examining some literature data it was found that in certain situations the FS parameter can result in better fatigue life predictions if the maximum normal stress is normalized by shear stress range instead. These data include uniaxial loadings with large tensile mean stress, and some non-proportional axial-torsion load paths with different normal-shear stress interactions. This modification to the FS parameter was investigated by using fatigue data from literature for 7075-T651 aluminum alloy, as well as additional data from 2024-T3 aluminum alloy fatigue tests performed in this study.